2016
DOI: 10.1016/j.ces.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and mass transfer modeling of carbon dioxide absorption into aqueous 2-piperidineethanol

Abstract: Amine scrubbing is a necessary technology to offset CO 2 emissions from fossil-fuel power plants. Of the many solvents studied, hindered amines are of particular interest for their marriage of the capacity of tertiary amines with rates a hundredfold greater than tertiary amines. The relatively rapid rates of hindered amines have not been adequately explained, despite their extensive use in commercial solvents. This work seeks to explain the rapid rate of mass transfer of 2-piperidineethanol (2PE) and uses this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Several studies on aqueous substituted piperidine + CO 2 mixtures by NMR have been reported. Sherman et al 22 studied 2-piperidineethanol as a candidate for carbon capture purposes and found it to form carbamates. Shin et al 7 reported that 2-MP absorbs CO 2 faster than monoethanolamine (MEA), the gas-processing industry standard, but did not observe the formation of carbamates for 2-MP.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on aqueous substituted piperidine + CO 2 mixtures by NMR have been reported. Sherman et al 22 studied 2-piperidineethanol as a candidate for carbon capture purposes and found it to form carbamates. Shin et al 7 reported that 2-MP absorbs CO 2 faster than monoethanolamine (MEA), the gas-processing industry standard, but did not observe the formation of carbamates for 2-MP.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several efforts to describe the chemical absorption of post combustion CO 2 from the flue gases of both coal-and gas-fired power plants. These models have either been developed on the assumption of equilibrium or rate-based mass transfer with some having been validated on pilot-scale plants Dutta, et al, 2017;(Sherman, et al, 2016;Norouzbahari, et al, 2016;Oko, et al, 2015). Although rate-based process simulation is well-known to provide more insight into the absorption process enabling the engineers to size the equipment and evaluate the process operating conditions more accurately (Sharifzadeh & Shah, 2015;Krishnamurthy & Taylor, 1985b;Krishnamurthy & Taylor, 1985a), equilibrium simulation, owing to its relative simplicity, provides useful insight on the viability of the process if used astutely.…”
Section: Introductionmentioning
confidence: 99%
“…The development of theoretical thermodynamic model for amine‐H 2 O‐CO 2 system, which is crucial in process design, simulation, and optimization, requires VLE data to incorporate chemical reactions and physical transfer . The model is supposed to correlate experimental data and make reasonable predictions for the related studies.…”
Section: Introductionmentioning
confidence: 99%
“…11 The development of theoretical thermodynamic model for amine-H 2 O-CO 2 system, which is crucial in process design, simulation, and optimization, requires VLE data to incorporate chemical reactions and physical transfer. [12][13][14][15][16] The model is supposed to correlate experimental data and make reasonable predictions for the related studies. Kent and Eisenberg developed a classic semi empirical model for acid gas CO 2 and H 2 S absorption in MEA and DEA aqueous solution.…”
mentioning
confidence: 99%
See 1 more Smart Citation